Currency option pricing and realised volatility - Manzur, Meher; Hoque, A.; Poitras, G. (Central Connecticut State University, Department of Finance, 2010)
Volatility is a key parameter in currency option pricing. This paper examines alternative specifications ofthe volatility input to the Black-Scholes option pricing procedure. The focus is the relative performance ofimplied, realized, and GARCH-based models as predictors of market volatility to forecast currency optionsprices. Using exchange-traded, daily and intra-daily data for three major European currencies, the results indicate that the realized volatility model tends to outperform the other two specifications, both in-sample and out-of-sample. This result is intuitively appealing and expected to facilitate resolution of other problems in risk management applications.